Analisis Mikroplastik Pada Air Dan Sedimen Di Pantai Teluk Lampung Dengan Metode Ft-Ir (Fourier Transform Infrared) - Eva Octarianita; Endang Linirin Widiastuti; Tugiyono Tugiyono (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Plastic is a packaging that is widely used in various sectors of life. Plastic waste that has long been polluted in the waters will degrade into small plastic particles called microplastics. This study aims to determine the presence of microplastic content in water and sediment at Teluk Lampung Beach, Pesawaran Regency, Lampung Province. Sampling water and sediment was carried out at three different stations Tegal Island, Pasaran Island, and Sebalang Pier. There are four types of microplastics found fiber, fragment, granule and film. The water sample found the highest pollution with an average of 16 ind/m3 and in the sediment sample the highest pollution with an average of 180 ind/kg. The results FT-IR founds polyhlyene (PE), polythelyene therapthalate (PET), Polypropylene (PP), polystes (PES), dan polyethylene terephthalate (PETE).